PEMANFAATAN MODEL PEMBELAJARAN INTERAKTIF BERBASIS PAPAN DIGITAL UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI SISWA PADA PEMBELAJARAN IPS KELAS VII SMP NEGERI 4 MADIUN - Damayanti, Rita; Maria, Yuli; Rahma Kusumastuti, Windhy; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research evaluates the outcomes of efforts to enhance collaborative abilities following the adoption of a digital board-based interactive learning approach. The study employs Classroom Action Research (CAR), which encompasses four phases: planning, implementation, observation, and reflection. Conducted across two cycles—Cycle I and Cycle II—it uses the pre-cycle stage as a baseline and initial reference point. The participants comprised 31 seventh-grade students from SMP Negeri 4 Madiun, including 16 boys and 15 girls. The research followed the procedural framework of the Kemmis and McTaggart model over the two cycles. Data were collected through observation activities involving students, utilizing instruments such as test question observation sheets. The findings revealed an improvement in collaboration skills following the introduction of the digital board-based interactive learning model. In Cycle I, students' collaboration skills rose to 73.54%. In Cycle II, these skills further improved to 87.35%. These results indicate that the digital board-based interactive learning approach effectively enhances students' teamwork abilities and educational achievements. Therefore, this study can be a recommendation and become an alternative choice for teachers to implement and improve the quality of learning in the classroom